Penerapan Model Problem Based Learning Untuk Meningkatkan Pemahaman Konsep Fisika Siswa SMA Negeri 1 Gunungsari - Ubaidilah, Achsin (Journal of Science and Mathematics Education, 2025)
This study aims to determine the effectiveness of applying the Problem-Based Learning (PBL) model in enhancing students' conceptual understanding of physics at SMA Negeri 1 Gunungsari. Problems in physics learning are often related to the low level of conceptual understanding, which results from conventional teaching approaches that lack active student engagement. The PBL model offers a student-centered learning approach, in which students are presented with contextual problems that encourage them to think critically, seek information, and build understanding through discussion and group work. This research employed a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of two grade XI science classes selected purposively: one class served as the experimental group using the PBL model, while the other class served as the control group with a conventional learning method. The analysis results showed a significant improvement in conceptual understanding in the experimental group compared to the control group. The average posttest score of the experimental group was statistically higher, and the N-Gain value increase demonstrated the effectiveness of PBL in fostering students' conceptual understanding. These findings indicate that the implementation of the PBL model can be an effective alternative learning strategy to improve the quality of physics education at the senior high school level.